Determinants Of Going Concern Audit Opinion: Company Size As A Moderation Variable - Pakilaran, Emanuela Yovita; Imam Subekti (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to demonstrate the effect of leverage, company growth, and mandatory disclosure on going concern audit opinions, with company size as a moderating variable. The issue addressed is the uncertainty faced by companies in maintaining their survival, particularly amidst the economic conditions following the Covid-19 pandemic. The purpose of this study is to provide empirical evidence regarding the influence of these factors on going-concern audit opinions and to explore the role of company size in moderating this influence. The population in this study was all companies listed on the IDX during 2021-2023. The sample was selected using a purposive sampling method, resulting in 131 manufacturing companies. The method used was Hierarchy Regression Analysis, which found that leverage had a positive effect, company growth and mandatory disclosure had no effect. Company size is proven to strengthen the influence of company growth and mandatory disclosure on going concern audit opinion, but does not moderate the influence of leverage on going concern audit opinion.